2012
DOI: 10.5534/kja.2012.30.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Recover Erectile Function Spontaneously after Cavernous Nerve Injury? Time-Dependent Structural and Functional Changes in Corpus Cavernosum Following Cavernous Nerve Injury in Rats

Abstract: = Abstract =Purpose: There has been a scarcity of integrated, long-term (>4 week) studies on structural and functional alterations in the penis according to the period following cavernous nerve (CN) injury. The aim of this study was to investigate time-dependent structural and functional changes in the corpus cavernosum following CN injury in a rat model. Materials and Methods:Ninety male Sprague-Dawley rats (10 weeks old) were divided into 4 groups: normal control (C), sham (S), bilateral CN resection (R), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…In the present study, we found that treatment with nano-DHA resulted in the recovery of erectile function as defined by increases in ICP, MAP, and other functional measures. The functional status in terms of maximum ICP/MAP following CN injury was 35% at 28 days post-injury in the vehicle group, which is consistent with previous studies in this model 8 12 . The maximum ICP/MAP was increased to 64% following injury in the 50 μg/kg nano-DHA group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we found that treatment with nano-DHA resulted in the recovery of erectile function as defined by increases in ICP, MAP, and other functional measures. The functional status in terms of maximum ICP/MAP following CN injury was 35% at 28 days post-injury in the vehicle group, which is consistent with previous studies in this model 8 12 . The maximum ICP/MAP was increased to 64% following injury in the 50 μg/kg nano-DHA group.…”
Section: Discussionsupporting
confidence: 91%
“…Both smooth muscle cell actin and collagen play an important role in fibroblast contractility 13 . The ratio of smooth muscle cells to collagen content is progressively reduced following CN injury or resection, indicating the increasing severity of fibrosis post-injury 8 . Indeed, bilateral CN ablation has been reported to induce fibrosis by reducing the number of smooth muscle cells and increasing collagen synthesis 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time‐dependent recovery of penile haemodynamics and histological structure alterations in the present study were also reported in crush models . Kim et al.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have reported that the 1-, and 4-, and 12-week intervals represent the acute, subacute, and chronic phases following CN injury, respectively. 31,32 Yang et al 7 have shown that phenotypic transformation occurs in CCSMCs at 12 weeks after CN injury. In our study, downregulated a-SMA and upregulated vimentin indicated the phenotypic transformation of CCSMCs can occur at the fourth week after CN injury.…”
Section: Discussionmentioning
confidence: 99%